IMPLEMENTASI NILAI NILAI PANCASILA DAN IMPLIKASINYA TERHADAP MAHASISWA SEBAGAI “AGENT OF CHANGE” - Prambudi, Yunike Dita; Najicha, Fatma Ulfatun (RONTAL: Jurnal Keilmuan Pancasila dan Kewarganegaraan, 2022)
Indonesia is a unitary state consisting of various tribes and nations based on Pancasila as the basis of the state. Pancasila as the basis of the state must be implicated and realized in all community actions, including in tertiary institutions. Higher Education was formed in the context of educating the nation's life through students who have character in them, Students have a role as "agents of change" so students must be able to apply and practice Pancasila as a guideline for social life and academic life. Students are expected to develop as individuals who have a broad intellect, are creative, confident, innovative and have good social relations and a great enthusiasm to contribute to society, nation and state. This study aims to provide information about the importance of influence and how to apply Pancasila values to students who have the role of agents of change in Indonesia. This research method uses literature study by reading and searching from books, journals, and other literature study sources that are relevant to the subject matter and issues to be discussed.